Discrete breathers in an one-dimensional array of magnetic dots - Pylypchuk, R.L.; Zolotaryuk, Y. (Физика низких температур, 2015)
The dynamics of the one-dimensional array of magnetic particles (dots) with the easy-plane anisotropy is
investigated. The particles interact with each other via the magnetic dipole interaction and the whole system is
governed by the set of Landau–Lifshitz equations. The spatially localized and time-periodic solutions known as
discrete breathers (or intrinsic localized modes) are identified. These solutions have no analogue in the continuum
limit and consist of the core where the magnetization vectors precess around the hard axis and the tails
where the magnetization vectors oscillate around the equilibrium position.